Design and characterization of nanostructured SERS substrates based on gold nanostars - V.O. Yukhymchuk; O.M. Hreshchuk; M.Ya. Valakh; Ye.G. Gule; M.A. Skoryk; V.S. Efanov; N.A. Matveevskaya; T.G. Beynik (Semiconductor Physics, Quantum Electronics & Optoelectronics, 2017)
Using the method of chemical synthesis, effective SERS substrates were developed, which were the films of gold nanoparticles possessing the form of stars. The peculiarity of star-shaped nanoparticles is that they could enhance the electric field of the radiating dipole not only by setting the frequency of the plasmon absorption band at the frequency of the exciting laser radiation, but additionally due to significant contribution to Raman scattering of the so-called “hot spots” that exist at the edges of the stars. “Nanostar”-based films were prepared using both direct deposition of gold nanoparticles from colloidal solution on the glass substrate and on the layer of polycation of polydiallyldimethyl ammonium bromide on the surface of glass substrates. Surface morphology of the obtained films was investigated using scanning electron microscopy. Plasmon absorption spectra were obtained using the method of optical absorption. Variation of geometrical parameters inherent to these nanostructures allows configuring the position of the plasmonic absorption band maximum close to the laser excitation wavelength. The coefficient of enhancement of Raman signal was evaluated for Rhodamine 6G molecules deposited on the designed SERS substrates (for different wavelengths of the exciting laser radiation, namely:  = 633, 532 and 457 nm).